2019
DOI: 10.1021/acs.orglett.9b00907
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Catalyzed Alkene Aminosulfonylation with Sodium Sulfinates For the Synthesis of Sulfonylated Pyrrolidones

Abstract: A copper-catalyzed direct aminosulfonylation of unactivated alkenes with sodium sulfinates for the efficient synthesis of sulfonylated pyrrolidones is described. This reaction features good functional group tolerance and wide substrate scope, providing an efficient and straightforward protocol to access this kind of pyrrolidones. Moreover, preliminary mechanistic investigations disclosed that a free-radical pathway might be invovled in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“… [11] The reaction tolerated a variety of functional groups regarding both of the functionalization partners under AgNO 3 /K 2 CO 3 catalytic system. A similar aminosulfonylation between alkene with sodium sulfinates was previously reported by Rao's group for the synthesis of sulfonylated pyrrolidones through the combination of Cu(OAc) 2 and Ag 2 CO 3 system [12] …”
Section: Silver‐mediated Two‐component Alkene Functionalization Reactmentioning
confidence: 53%
“… [11] The reaction tolerated a variety of functional groups regarding both of the functionalization partners under AgNO 3 /K 2 CO 3 catalytic system. A similar aminosulfonylation between alkene with sodium sulfinates was previously reported by Rao's group for the synthesis of sulfonylated pyrrolidones through the combination of Cu(OAc) 2 and Ag 2 CO 3 system [12] …”
Section: Silver‐mediated Two‐component Alkene Functionalization Reactmentioning
confidence: 53%
“…Control experiments proved the radical nature of the developed process [231] . Using the Cu(OAc) 2 /Ag 2 CO 3 system in DMF at 100 °C, 5‐sulfonylmethyl γ‐lactams were obtained from aliphatic unsaturated amides and aromatic sodium sulfinates in 55–85% yields [232] . The reaction of 1,6‐enynes 419 with sulfonyl hydrazides 420 under oxidative conditions gave γ‐lactams 421 with (Z) / (E) ratio of 1:1 to 5:1.…”
Section: Sulfonylation Followed By Cyclizationmentioning
confidence: 87%
“…Rao et al , reported a copper-catalyzed direct aminosulfonylation of unactivated alkenes with sodium sulfinates for the efficient synthesis of sulfonylated pyrrolidones via a 5- exo cyclization process ( Scheme 209 ). 316 Generally, the unsaturated quaternary amides reacted smoothly with sodium arylsulfinates and afforded the corresponding aminosulfonylation products in good to high yields. The reaction of α-substituted quaternary amides also generated the desired products in good yields with low diastereoselectivity ratios.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%